PENGARUH BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO), NON PERFORMING LOAN (NPL) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP TINGKAT PROFITABILITAS PADA BPR KONVENSIONAL NTB LOMBOK TIMUR TAHUN 2013-2017 - Muhammad Amin (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2018)
At this research aim to to know what is there is influence [among/between] Earnings of Oprasional and Burden Operational (BOPO), Non Performing Loan (NPL) and of Loan Deposit Ratio to (LDR) To Return On Asset (ROA) at] Conventional BPR of Sub-Province Lombok island East year 2013-2017. Population which is used in this research is all conventional BPR of Lombok island year east sub-province 2013-2017. By using method of Sampel  Saturated,  taken  by  of  sampel  counted  3  bank  which  enlist  in  OJK.  Technique Analysis the used is doubled linear regresi, test classic assumption covering test of normlitas, test autokorelasi., test test and heteroskedastisitas of mult ikolinearitas. Afterwards also test hypothesis use t- statistical to test coefficient of regresi parsial, and also F- statistical to test influence by together with level 5% (0.05Keywords : Burden Operate for to Earnings Of Operation (BOPO), Non Performing Loan (NPL), Loan To Deposit Ratio (LDR), Return On Assets (ROA)